Conduction Block and Nerve Cross-Sectional Area in Multifocal Motor Neuropathy - Li, Yi; Niu, Jingwen; Liu, Tanxin; Ding, Qingyun; Wu, Shuang; Guan, Yuzhou; Cui, Liying; Liu, Mingsheng (Frontiers in Neurology, 2019)
Introduction: Motor nerve conduction block (CB) is the main electrophysiological feature of multifocal motor neuropathy (MMN). Increased cross-sectional area (CSA) can be detected by nerve ultrasound in MMN. In this study, we aim to analyze the correlation between CB and CSA in MMN. Methods: Twelve patients with MMN were recruited. Ultrasonography tests and motor nerve conduction studies (NCSs) were performed on median and ulnar nerves simultaneously. CSA was measured at 10 consecutive sites on those nerves, meanwhile nerves were traced continuously and recorded thoroughly under ultrasound. Results: In motor NCSs, 12 definite CB and 12 probable CB areas were detected across standard segments of median and ulnar nerves. With ultrasound studies, increased CSA was detected at 36 sites. There were 9 standard segments with CB and increased CSA, 15 segments with CB but normal CSA, and 27 segments with increased CSA but no CB. Discussion: In MMN, motor nerve CB was not always consistent with increased CSA.